2022
DOI: 10.3389/fmed.2022.916145
|View full text |Cite
|
Sign up to set email alerts
|

Main Pathological Changes of Benign Ureteral Strictures

Abstract: ObjectiveTo identify the pathological classification of benign ureteral strictures according to the histological features and explore the relationship between various pathological types and inflammatory cells, fibroblasts, and collagen.Patients and MethodsThirty one specimens from patients diagnosed with ureteral strictures between 2013 and 2021 were included and classified according to the histopathological characteristics. The number of fibroblasts and inflammatory cells was counted, and the proportion of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The identification of a lesser degree of HN as a risk factor for difficult ureter (DU) is thought to be related to the pathologic change in the ureter itself. In previous studies dealing with ureter pathology in difficult ureter [18,19], the pathology of ureter stricture has been reported to be related to inflammation, fibroplasia, hyalinization [18], polyp or granulation tissue growth secondary to stone, or other benign or neoplastic cause stricture [19]. In this study, a lesser degree of HN was identified as a risk factor for difficult ureter (DU), which is considered to be related to pathologic changes in the ureter itself, not to stone-related factors or clinical factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of a lesser degree of HN as a risk factor for difficult ureter (DU) is thought to be related to the pathologic change in the ureter itself. In previous studies dealing with ureter pathology in difficult ureter [18,19], the pathology of ureter stricture has been reported to be related to inflammation, fibroplasia, hyalinization [18], polyp or granulation tissue growth secondary to stone, or other benign or neoplastic cause stricture [19]. In this study, a lesser degree of HN was identified as a risk factor for difficult ureter (DU), which is considered to be related to pathologic changes in the ureter itself, not to stone-related factors or clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a lesser degree of HN was identified as a risk factor for difficult ureter (DU), which is considered to be related to pathologic changes in the ureter itself, not to stone-related factors or clinical factors. Although additional studies are needed, a low degree of HN can also be considered an indicator of ureter pathologic changes, as shown in the studies [18,19]. In addition, HN has been identified as a risk factor for DU, making surgery more difficult and resulting in worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation